RECQL1 and WRN DNA repair helicases: potential therapeutic targets and proliferative markers against cancers - Futami, Kazunobu; Furuichi, Yasuhiro (Frontiers in Genetics, 2015)
RECQL1 and WRN helicases in the human RecQ helicase family participate in maintaining genome stability, DNA repair, replication and recombination pathways in the cell cycle. They are expressed highly in rapidly proliferating cells and tumor cells, suggesting that they have important roles in replication of a genome. Although mice deficient in these helicases are indistinguishable from wild-type mice, their embryonic fibroblasts are sensitive to DNA damage. In tumor cells, silencing the expression of RECQL1 or WRN helicase by RNA interference (RNAi) induces mitotic catastrophe that eventually kills tumor cells at the mitosis stage of the cell cycle. By contrast, the same gene-silencing by cognate small RNA (siRNA) never kills normal cells, although cell growth is slightly delayed. These findings indicate that RECQL1 and WRN helicases are ideal molecular targets for cancer therapy. The molecular mechanisms underlying these events were studied extensively by us and others, which may help development of anticancer drugs free from adverse effects by targeting DNA repair helicases RECQL1 and WRN. As expected, the anticancer activity of conventional genotoxic drugs is significantly augmented by the combined treatment with RECQL1- or WRN-siRNAs that prevents DNA repair in cancer cell. In this review, we focus on studies that clarified the mechanism behind the specific killing of cancer cells and introduce efforts to develop anticancer RecQ-siRNA drugs free from adverse effects.